2001
DOI: 10.1081/ci-100103465
|View full text |Cite
|
Sign up to set email alerts
|

X-RAY FLUORESCENCE ESCAPE PEAKS IN Ge(Li) DETECTORS

Abstract: The escape peak-to-photopeak intensity ratios and escape fractions of characteristic K X-rays, as a function of incident radiation energy in the range 15.75-50 keV and collimator diameter (or area seen by the crystal ), are measured for a Ge(Li) detector. The experimental results are compared with theoretical predictions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…MCA spectra were typically recorded for an integration time of 120 s and normalized to I 0 for quantitative comparison. The excitation energy was systematically varied (a) to efficiently excite selected elements above their absorption thresholds, (b) to reduce the effect of overlapping elemental lines and (c) to clarify the effect of the characteristic escape peaks [33] -an artifact of the Ge solid state detector material, which interferes with low lying sample element lines in the MCA spectra due to fluorescence energy partially transferred to an ''escaping'' Ge Ka,b photon ($9.8 keV). XAFS scans at the Se, Zr, and Tc K and the U, Np, Pu and Am L3 absorption edges (corresponding 2p 3/2 binding energies for metal species: 17.166, 17.610, 18.057 and 18.510 keV, respectively) were recorded in step-by-step mode with a step width of 0.5 eV in the XANES regions and equidistant k-steps of 0.035 Å À1 in the EXAFS regions (where detection of extended spectral ranges was adequate, considering element concentrations).…”
Section: Xafs and Xrf Measurementsmentioning
confidence: 99%
“…MCA spectra were typically recorded for an integration time of 120 s and normalized to I 0 for quantitative comparison. The excitation energy was systematically varied (a) to efficiently excite selected elements above their absorption thresholds, (b) to reduce the effect of overlapping elemental lines and (c) to clarify the effect of the characteristic escape peaks [33] -an artifact of the Ge solid state detector material, which interferes with low lying sample element lines in the MCA spectra due to fluorescence energy partially transferred to an ''escaping'' Ge Ka,b photon ($9.8 keV). XAFS scans at the Se, Zr, and Tc K and the U, Np, Pu and Am L3 absorption edges (corresponding 2p 3/2 binding energies for metal species: 17.166, 17.610, 18.057 and 18.510 keV, respectively) were recorded in step-by-step mode with a step width of 0.5 eV in the XANES regions and equidistant k-steps of 0.035 Å À1 in the EXAFS regions (where detection of extended spectral ranges was adequate, considering element concentrations).…”
Section: Xafs and Xrf Measurementsmentioning
confidence: 99%
“…The authors once more confirmed that the escape peak separation was 1.740 keV, and suggested that higher figures (1.750 to 1.755) were almost certainly caused by account not being taken of the true complexity of the escape peak structure and overlapping peaks from other X ray interactions, such as radioactive Auger events. Escape peak-to-parent ratio and escape fractions in the energy range of 15.75 to 50 keV were also reported for the less-common Ge(Li) detector, 18 where the escape peak probabilities and the escape peak complexity are much greater than for Si (Li) detectors. The Si(Li) detector response function and detection efficiency over the energy range 0.1 to 5 keV were studied using monochromatised SR from the PTB beam line at BESSY in Berlin.…”
Section: Detectorsmentioning
confidence: 68%
“…We compared our results with those of other analytical calculations and Monte Carlo simulations, 14,15 which were in good agreement with the earlier measurements. 12 Also given in Table 1 are the results of a recent study, 17 which are generally higher than the rest. We believe this was because of detector efficiency corrections, which were not needed.…”
Section: Resultsmentioning
confidence: 84%